2021
DOI: 10.1109/access.2021.3083421
|View full text |Cite
|
Sign up to set email alerts
|

Security Hardening of Botnet Detectors Using Generative Adversarial Networks

Abstract: Machine learning (ML) based botnet detectors are no exception to traditional ML models when it comes to adversarial evasion attacks. The datasets used to train these models have also scarcity and imbalance issues. We propose a new technique named Botshot, based on generative adversarial networks (GANs) for addressing these issues and proactively making botnet detectors aware of adversarial evasions. Botshot is cost-effective as compared to the network emulation for botnet traffic data generation rendering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Authors in [23] compared 85 different oversampling techniques and suggested the three best-performing variants as SMOTE IPF, ProWSyn and polynom fit SMOTE. In [7], authors have compared the performance of these three SMOTE variants with GANs. Through empirical results, they found that GANs outperform the three mentioned oversamplers in most of the adversarial training of ML classifiers.…”
Section: B Data Oversampling and Gansmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors in [23] compared 85 different oversampling techniques and suggested the three best-performing variants as SMOTE IPF, ProWSyn and polynom fit SMOTE. In [7], authors have compared the performance of these three SMOTE variants with GANs. Through empirical results, they found that GANs outperform the three mentioned oversamplers in most of the adversarial training of ML classifiers.…”
Section: B Data Oversampling and Gansmentioning
confidence: 99%
“…The quantitative analysis of EVAGAN was performed on CC datasets. We have followed the work done by the authors in [7] for dataset selection of botnet. We have used three datasets, ISCX-2014, CIC-2017 and CIC-2018, from the Canadian Institute of Cybersecurity (CIC).…”
Section: B Data Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed from this table that we used 'sigmoid' in the output layer of G due to the reason that we wanted to generate the API data in which the values need to be between 0 and 1. We propose a GAN based methodology inspired by [20] that could mimic and generate the API based APK feature set. We propose the GAN evaluation by tweaking the classifier twosample test (C2ST) [21] for G performance evaluation.…”
Section: Evasion Attacks Generatormentioning
confidence: 99%